Nature monitoring: a tool for the evaluation of the preservation of synanthropic habitats - Bomanowska, Anna; Kirpluk, Izabella (Biodiversity: Research and Conservation, 2015)
The article presents the results of nature monitoring in synanthropic habitats. It shows the organizational aspects of monitoring, a survey procedure, including its assessment for use in synanthropic habitats, and the key findings of the research, including the evaluation of the conservation status of habitats covered by the monitoring and influencing factors’ effects. Observations of segetal and ruderal habitats were carried out in 2013 within the Kampinos National Park, according to the recommendations specified in the State Environmental Monitoring Programme, with specific adjustment to the monitored habitats. We used, for example, modified indices for specific structures and functions, e.g., by introducing the index of “archaeophytes”, which was also adopted as a cardinal index for synanthropic habitats. The obtained results show the detailed information, collected during monitoring, on the current status of synanthropic habitats. They allowed to evaluate conservation status, threats and conservation prospects for these habitats. This is the first proposal for the standardized monitoring of synanthropic habitats in Poland.